Experiences on GIS On-Site Evaluation Using High Sensitivity PD Techniques - Azcarraga, C.G.; Garcia-Colon, V.R. (2007 Large Engineering Systems Conference on Electric Power Engineering, 2007)
This document describes the development and practical field application of ultra high frequency partial discharge detection techniques used by Institute de Investigaciones Electricas in Mexico for PD monitoring of gas insulated substations. These techniques have been successfully applied on eleven GIS, allowing the Mexican main utility to plan predictive maintenance programs to avoid catastrophic failures. Two different diagnosis techniques had been used for GIS dielectric integrity on-line diagnosis: time domain and conventional phase resolved PD pattern analysis. Time domain technique has been used to assess PD source location. On the other hand, phase resolved PD patterns analysis was used to evaluate instrument transformers and also to determine which kind of defect is detected by the monitoring. Different PD coupling devices developed at the IIE, phase reference transducers and calibration issues are described too.